Persons with Diabetes’ Perceptions of Family Burden and Associated Factors - Israel Bekele Molla; Million Abera Berhie; Kebebe Adugna Debele; Gugsa Nemera Germossa; Fikadu Balcha Hailu (Journal of Diabetes Research)
Background. Families of a person with diabetes play a vital part in diabetes management since their support helps with regimen engagement in self-management behaviors. However, focal information on the family burden of diabetes is lacking. This study is aimed at, therefore, assessing the persons with diabetes’ perceptions of family burden and associated factors at a university hospital. Methods and Materials. A facility-based cross-sectional study design was conducted from July 26 to September 26, 2021on 403 persons’ with diabetes attending Jimma Medical Center diabetic clinic, the study sample was selected using a simple random sampling method. The data was collected using the Zarit burden questionnaire through face-to-face interviews. Descriptive statistics (mean, standard deviation, frequency, and percentages) were ordered logistic regression, and statistical significance was declared at P value ≤0.05. Results and Discussion. About 36.8% of the patient was in mild to moderate family burden of diabetes. Farmer (AOR 5.419; CI: 1.18, 24.872), living with partners and family (AOR: 0.110, CI: 0.018, 0.659), comorbidity (AOR 5.419; CI: 1.18, 24.872), oral hypoglycemic agent (AOR: 0.380, CI: 0.191, 0.758), and being never hospitalized before because of diabetes (AOR: 0.044, CI: 0.003, 0.571) was statistically associated with a family burden. Conclusion. About one-fourth of diabetic patient-perceived mild to the moderate family burden of diabetes, persons with diabetes who work as farmers and have comorbidities have a higher opinion of family burden, whereas those who live with partners or family members, use oral hypoglycemic medications, and have never been hospitalized for diabetes have a lower view of family burden due to diabetes. The results of this study suggest that strategies for health promotion, intervention, and prevention of diabetes at the family level should consider the interaction between family member burden and the patient’s sociodemographic and disease-related factors. A further large-scale study is required to validate these findings.